2003
DOI: 10.1073/pnas.2336648100
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an orf virus chemokine-binding protein: Shifting ligand specificities among a family of poxvirus viroceptors

Abstract: We identify a secreted chemokine inhibitor encoded by orf virus (ORFV), the prototypic poxvirus of the Parapoxvirus genus, and show that it is related to the poxvirus type II CC-chemokine-binding proteins (CBP-II) produced by members of the Orthopoxvirus and Leporipoxvirus genera. The ORFV chemokine-binding protein (CBP) is functionally similar to the CBP-II proteins in its ability to bind and inhibit many CC-chemokines with high affinity. However, unlike CBP-II, the ORFV CBP also binds with high affinity to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 47 publications
8
89
1
Order By: Relevance
“…11 Many viruses secrete proteins that bind chemokines as a means of evading the host immune system and ensuring their own survival. 12 Recently, a novel type of chemokine-binding protein (CBP) has been identified from orf virus, [13][14][15] and fellow parapoxviruses, bovine papular stomatitis virus (BPSV), and pseudocowpox virus. 16,17 This CBP shows high-affinity binding for both human and mouse CC, CXC, and C chemokines and has been demonstrated to prevent inflammatory monocyte recruitment to the skin and to block dendritic cell trafficking to peripheral lymph nodes.…”
Section: February 2015mentioning
confidence: 99%
“…11 Many viruses secrete proteins that bind chemokines as a means of evading the host immune system and ensuring their own survival. 12 Recently, a novel type of chemokine-binding protein (CBP) has been identified from orf virus, [13][14][15] and fellow parapoxviruses, bovine papular stomatitis virus (BPSV), and pseudocowpox virus. 16,17 This CBP shows high-affinity binding for both human and mouse CC, CXC, and C chemokines and has been demonstrated to prevent inflammatory monocyte recruitment to the skin and to block dendritic cell trafficking to peripheral lymph nodes.…”
Section: February 2015mentioning
confidence: 99%
“…This relationship is primarily due to sequence similarity found between the GIF protein and a chemokine-binding protein also encoded by the PPVs (ORF 112). This protein has been shown to be related to the vaccinia virus (VACV) chemokine-binding protein C23L and to possess both Cand CC-chemokine-binding activity (Seet et al, 2003). As we did not find any GM-CSF-or IL-2-binding activity with the BPSV GIF protein, we investigated whether the GIF proteins exhibited CC chemokine-binding activity.…”
Section: Discussionmentioning
confidence: 97%
“…It had previously been suggested that the ORFV GIF protein showed significant similarity to a family of poxvirus chemokine-binding proteins; more specifically, those found in members of the genera Orthopoxvirus and Leporipoxvirus that bound a variety of CC chemokines (Seet et al, 2003). In addition, significant similarity was also found between it and another ORFV protein, encoded by a gene found upstream of the GIF gene in the ORFV genome.…”
Section: Investigation Of Chemokine Binding By Ppv Gifsmentioning
confidence: 97%
See 1 more Smart Citation
“…The OVIFNR gene has interferon resistance function which frankly signifies the crucial role of interferon in host resistance to Orf virus infected animals (Haig and Mercer, 1998). The Orf virus synthesizes virus encoded cytokine binding protein (vCBP) discovered by Counago et al, (2010), that competitively inhibits binding site on the receptors of homogenous cytokines (Seet et al, 2003) and inhibits inflammation by preventing monocytes and DCs from transferring into the skin inflammatory lesions or peripheral lymph nodes. The ORFV121 encodes a novel NF-κB inhibitor thus inhibits the phosphorylation and nuclear translocation of NF-kB-p65 thereby culminating the translation of the host immune-related genes.…”
Section: Virus Virulence Factors and Evasion Of Host Immunitymentioning
confidence: 99%